THE EFFECTIVENESS OF TREATMENT AND REHABILITATION OF CANCER PATIENTS AS THE MOST IMPORTANT CRITERION FOR IMPROVING THE QUALITY OF LIFE - Петров, Андрей Георгиевич; Хорошилова, Ольга Владимировна; Семенихин, Виктор Андреевич; Филимонов, Сергей Николаевич; Вайман, Евгений Федорович; Григорьева, Елена Борисовна (Medicine in Kuzbass, 2023)
Modern approaches to the organization of specialized medical and pharmaceutical care are important in the treatment and prevention of oncological diseases. Preventive measures in the state of pre-illness, the creation and implementation of specialized pharmaceutical care as a theory and practice in the treatment and prevention of oncological diseases are of particular importance. The development of pharmacoprophylactic programs within the framework of specialized medical and pharmaceutical care is currently extremely relevant in solving the problem of oncological diseases. The main and strategic direction of health care is preventive, implementing progressive ideas and principles of social policy and strategies for public health protection. Emphasis on preventive measures in the fight against oncological diseases, where sanitary-epidemiological, hygienic and other medical and medico-technical preventive measures carried out on a nationwide scale are of paramount importance.